2009
DOI: 10.1002/elps.200800673
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the separation of macromolecules: A review of current computer simulation methods

Abstract: Theory and numerical simulations play a major role in the development of improved and novel separation methods. In some cases, computer simulations predict counterintuitive effects that must be taken into account in order to properly optimize a device. In other cases, simulations allow the scientist to focus on a subset of important system parameters. Occasionally, simulations even generate entirely new separation ideas! In this article, we review the main simulation methods that are currently being used to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
131
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 277 publications
1
131
0
Order By: Relevance
“…Our simulations used coarse-grained Langevin Dynamics 41 . We modelled fd as a generic linear polymer composed of 133 beads of diameter s, giving the correct aspect ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Our simulations used coarse-grained Langevin Dynamics 41 . We modelled fd as a generic linear polymer composed of 133 beads of diameter s, giving the correct aspect ratio.…”
Section: Resultsmentioning
confidence: 99%
“…However, a detailed physical understanding of surface transport of DNA is currently not available. 3 For example, it is commonly known that the diffusion coefficient of DNA decreases with increase in DNA size in free solution 4 and under two-dimensional confinement. 5 However, a recent experimental study on electrophoresis of DNA on an atomic force microscopy surface showed the faster movement of longer DNA in a thin pure water film.…”
mentioning
confidence: 99%
“…From a simulation point of view, modeling such a system is a challenging task, because both the electrostatic and hydrodynamic interactions are long-range. Taken separately, each interaction has been well studied in the literature [6][7][8][9][10][11]. Methods can be grouped into the categories of "implicit" and "explicit" methods, [9,10], depending on whether the small components (solvents and ions) are simulated explicitly or replaced by effective interactions between large components.…”
Section: Simulation Methodsmentioning
confidence: 99%